Combined Anterior-Posterior Fusion Versus Posterior Alone Fusion for Cervical Myelopathy in Athetoid-Cerebral Palsy. Issue 8 (October 2022) - Kim, Gang-Un; Ahn, Myun-Whan; Lee, Gun Woo
Study Design: Retrospective comparative study. Objectives: Although some studies have discussed the use of lateral mass screws (LMSs) in patients with cerebral palsy (CP), it is unclear whether posterior LMS fixation alone is a suitable method. We aimed to compare the clinical, radiological, and surgical outcomes of 2 surgical modalities, namely, combined anterior-posterior (A-P) instrumented fusion and posterior fusion alone, in athetoid-type CP patients with cervical myelopathy (CM). Methods: We analyzed 63 patients with athetoid-CP and CM who underwent posterior fusion only with LMS (group A, 35 patients) and A-P fusion (group B, 28 patients). The primary outcome was the 1- and 3-year fusion rates for the surgical segments. The secondary outcomes included the clinical outcomes based on pain intensity determined using the visual analog scale score, neck disability index, and 17-point Japanese Orthopedic Association score, radiological, and surgical outcomes. Results: Fusion was achieved at 3 years postoperatively in 22 of 35 patients (63%) in group A and in 26 of 28 patients (93%) in group B ( P = 0.02). The posterior neck pain intensity was also significantly lower in group B than in group A 2 and 3 years postoperatively ( P = 0.02 and 0.01, respectively). The incidence of screw loosening and implant-related problems was higher in group A (60%) than in group B (21%) ( P = 0.01). The other clinical and radiological parameters were similar between the groups. Conclusions: For athetoid CP-induced CM, combined A-P fusion would result in superior clinical and radiological outcomes compared to posterior fusion alone.